Institutionalizing Neoliberalism: 21st‐Century Capitalism, Market Sprawl, and Social Policy in the United States. Issue 1 (March 2016) - Caplan, Mary A.; Ricciardelli, Lauren
Abstract: Neoliberalism is a foundational expression of 21st‐century capitalism. This article advances critiques of neoliberal influences on social welfare in the United States by detailing how core neoliberal principles such as individualism, freedom of choice, rationality, self‐interest, utilization of market mechanisms, and non‐intervention of the state have become institutionalized in contemporary social services as (i) welfare capitalism, (ii) privatization, (iii) contract service delivery, (iv) individual savings strategies, (v) voucher systems, (vi) consumer‐directed spending, and (vii) labor market activation. The authors provide an overview of capitalism and classic economic liberalism as incubators of neoliberalism and describe each mechanism and propose a framework to visualize their interrelated structure. As indicators of market sprawl, these mechanisms express and perpetuate deep market involvement in the health and human service sector. It is argued that the neoliberal institutionalization of social services is antithetical to the goals of a modern welfare system, and instead creates punitive and restrictive programs and policies. Recommended actions include critique and empirical examination of how market mechanisms influence the social services sector, specifically regarding the intermediary role of government‐funded private sector service provision.